O combate à corrupção no direito administrativo e os acordos de leniência: a experiência do Tribunal de Contas da União - Mancini, Margarida Isabella Malena (2021)
This research seeks to initially draw an overview of the topic of corruption today, as well as the mechanisms used to fight it, following the Leniency Agreement under the Anti-Corruption Law (LAC) as a legal formatting instrument in meeting the objective to remedy illegal practices, addressing the requirements of these adjustments and public entities legitimated to sign them. Through a deductive analysis, as well as doctrinal research and technical articles, bringing up the current jurisprudence, it is intended to clarify the institute of the Leniency Agreement, bringing reflections aimed at establishing possible solutions that allow the effective performance of the protagonist bodies of the institute, without losing its institutional characteristics, but asserting the main function of leniency agreements, in the search for compensation to the treasury and combating criminal practices of corruption.